Circ_0110498 facilitates the cisplatin resistance of non‐small cell lung cancer by mediating the miR‐1287‐5p/RBBP4 axis. Issue 7 (23rd January 2023) - Hao, Dexun; Li, Yanshuang; Shi, Jiang; Jiang, Junguang
Abstract: Background: Circular RNAs (circRNAs) play vital roles in non‐small cell lung cancer (NSCLC) progression. Our research analyzed the role of circ_0110498 on the cisplatin (DDP) resistance of NSCLC. Methods: Cell glycolysis was analyzed by measuring glucose consumption and lactate production. Protein expression was determined by western blot analysis. The expression of circ_0110498, microRNA (miR)‐1287‐5p and RBBP4 was detected by RT‐qPCR assay. Cell counting kit‐8, colony formation and transwell assays, together with flow cytometry were conducted to analyze cell DDP resistance, proliferation, metastasis and apoptosis. Results: Circ_0110498 expression was elevated in DDP‐resistant NSCLC tissues and cells. Circ_0110498 silencing not only suppressed the DDP resistance of NSCLC cells by inhibiting cell growth, metastasis and glycolysis, but also enhanced the DDP sensitivity of NSCLC tumors. MiR‐1287‐5p was sponged by circ_0110498, and its inhibitor also reversed the effect of circ_0110498 silencing on the DDP resistance of NSCLC cells. MiR‐1287‐5p interacted with RBBP4, and RBBP4 overexpression partly reversed the inhibitory effect of miR‐1287‐5p on the DDP resistance of NSCLC cells. Conclusion: Circ_0110498 facilitated DDP resistance partly through mediating the miR‐1287‐5p/RBBP4 signaling in NSCLC. Abstract : Circ_0110498 facilitated DDP resistance via the miR‐1287‐5p/RBBP4 axis in NSCLC.